Extraction of Chlorophyll from Alfalfa Plant - Kamal, Isam; Jawad, Dr.Ahmed; Al-Jomaily, Ali Khalid Khudair (Al-Khwarizmi Engineering Journal, 2017)
The extraction process of chlorophyll from dehydrated and pulverized alfalfa plant were studied by percolation method. Two  solvent systems were used for the extraction namely; Ethanol-water and Hexane-Toluene systems . The effect of circulation rate, solvent concentration, and solvent volume to solid weight ratio were studied. In  both ethanol water, and Hexane-Toluene systems it appears that solvent concentration is the most effective variable.